Role of USG and diuretic renogram in evaluation of outcome in children after Anderson-Hynes dismembered pyeloplasty for unilateral PUJ obstruction (Journal of Paediatric Surgeons of Bangladesh, 2023)
Introduction: Pelvi-ureteric junction (PUJ) obstruction is one of the most common causes of Hydronephrosis in paediatric population. Anderson Hynes dismembered pyeloplasty is the standard surgical treatment of PUJ obstruction. Ultrasonogram (USG) and isotope renogram are widely used to assess the success of pyeloplasty. Changes in the anteroposterior diameter (APD) of renal pelvis, renal cortical thickness (CT) in USG and split renal function (SRF) in DTPA renogram can determine the postoperative outcome following pyeloplasty. Aim of the study: The aim of this study was to see the changes in APD, CT and split renal function after pyeloplasty.Materials and Methods: A quasi experimental study was done among children with unilateral PUJ obstruction who underwent open Anderson-Hynes dismembered pyeloplasty from January 2020 to December 2021 at Bangladesh Shishu Hospital and Institute. All patients were evaluated with ultrasonography at 6 months and DTPA after 1 year of operation. Changes AP diameter of renal pelvis, renal parenchymal thickness and SRF were recorded to assess the prognosis. Increase of SRF, more than 5% on the obstructed side compared with preoperative result was regarded as significant improvement. A change in SRF of within 5% of the preoperative level was defined as stable renal function and a decrease of SRF >5% of the preoperative level was considered as deteriorating renal function. Results: In the present study, we enrolled 30 patients. Mean age of the patients was 25.80 months. The mean APD was 44.03 mm preoperatively and 31.03 mm after 6 months of pyeloplasty. The mean CT was 3.24 mm preoperatively and 6 months after operation it was 4.77 mm. The comparison of mean changes of APD and CT revealed significant. Postoperative renal SRF increased 6.04% (± 7.39%) than preoperative SRF value which was statistically significant.Conclusion: Changes of renal APD (Anteroposterior diameter) and CT (cortical thickness) and Split renal function occur after pyeloplasty. So USG and DTPA can be used to assess the outcome of pyeloplasty in children with unilateral PUJ obstruction.Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1 & 2): 3-7